Estimation of fetal weight near term: comparison between ultrasound and symphysis-fundus evaluation by Johnson's rule. (3rd April 2021) - Ricchi, Alba; Pignatti, Lucrezia; Bufalo, Elisa; De Salvatore, Claudia; Banchelli, Federico; Neri, Isabella
Abstract: Introduction: The fetal weight estimation is commonly performed by ultrasound but the manual method is also applied in developing countries due to the lack of scan availability and in western countries for the management of low-risk pregnancy managed autonomously by the midwives. The most applied method to estimate fetal weight measures the longitudinal diameter of the symphysis-fundus according to Johnson's rule. The aim of the present study is to evaluate the reliability of the symphysis-fundus method with respect to the ultrasound to estimate fetal weight in low risk pregnancies according to the classification of adequate, small and large for gestational age. Materials and methods: Two hundred twenty low-risk women referred to the clinic for the management of term pregnancy were enrolled for the study. The following data were collected: age, body mass index, parity, values of symphysis-fundus evaluation according to Johnson's rule, ultrasound fetal weight estimation values, and birthweight. Results: Considering the whole sample, fetal weight was estimated similarly by the manual method and with the ultrasound (79.5 versus 85% of the cases; n.s.). However, in overweight women, the ultrasound better estimates fetal weight in respect to manual method (94.4 versus 80.3% of the cases; p < .02) and similarly in obese women also ultrasound performed better in comparison to manual method (91.8 versus 71.4% of the cases; p < .01). Conclusions: The manual evaluation could be considered a reliable method to assess fetal weight for the management of low-risk pregnancies near term to optimize the resources and also offer a safe nonmedical approach. Further studies should clarify the accuracy of the manual method to estimate fetal weight in overweight and obese women, also considering the great increase of the obesity incidence in the obstetric population.